Biotic stability of Scots pine growing in stands on fairly fertile soil types of the Lviv Roztochya - Hryhoriy Krynytskyy; Ihor Skolsky; Olga Krynytska; Natalia Lutsiv; Volodymyr Yakhnytsky (Наукові праці Лісівничої академії наук України, 2021)
In recent years in Ukraine and other European countries, there has been observed a decrease in biotic resistance and mass drying of pine stands. The ecological precondition for this drying off is global climate change and related fluctuations, primarily, of the temperature and hydrological regimes. At the same time, the tremendous ecological, economic and social importance of pine stands necessitates a thorough study of forest site conditions, particularly of phytocenotic ones. They are the most viable and have high biotic stability.